Protonated water clusters in TPC's - Kaya, Y.; Kalkan Y.; Veenhof R. (Elsevier B.V., 2016)
Water vapour is added to the ALICE TPC gas to enhance its stability. These polar molecules create large protonated water clusters around a H+ core. In this context, the reactions H3O+ (H2O)n-1+H2O?H3O+ (H2O)n (n=1-9) were studied in the gas phase. Structures for these clusters are suggested and the most stable structures for each cluster size are shown. The thermodynamic parameters ?Hn-1,n0, ?Gn-1,n0, ?Sn-1,n0 and equilibrium constants Kn-1,n for the reaction were calculated to determine the size of the water clusters. The results are close to experimental data found in the literature. Protonated water clusters at stp have a size of 6-9 which corresponds to a mass of 127.1-181.2g/mole. © 2015 Elsevier B.V.
Keywords: DFT Calculations; Gas Detectors; Protonated water cluster; Thermodynamic Parameters